Chemoprevention of fibroid tumors by [-]-epigallocatechin-3-gallate in quail - Ozercan, Ibrahim H.; Şahin, Nurhan; Akdemir, Fatih; Onderci, Muhittin; Seren, Soley; Şahin, Kazım; Küçük, Ömer (Pergamon-Elsevier Science Ltd, 2008)
Spontaneous leiomyomas of the oviduct are common tumors of the Japanese quail (Coturnix coturnix japonica), and fibroid tumors in the laying hen are similar to human fibroid tumors with respect to estrogen and progesterone receptors. This makes the quail a good animal model for screening potential agents for that aid in the prevention and treatment of human myoma uteri. We have previously reported a decreased incidence of leiomyomas in the oviduct of Japanese quail with antioxidant supplementation, for example, lycopene and soy isoflavones. Most of the health benefits associated with green tea consumption is attributed to EGCG, one of 4 major catechins found in green tea. This study investigated the effects of epigallocatechin-3-gallate supplementation on the development of leiomyomas in the oviduct of Japanese quail. We also measured serum and tissue levels of malondialdehyde and TNF-alpha. One hundred eighty quail (8 months old) were assigned to 3 treatment groups consisting of 6 replicates of 10 quail in each group. Animals were fed either a basal diet (control group) or the basal diet supplemented with 200 or 400 mg of EGCG/kg of diet. The animals were euthanized at the end of the 12-month study period, and the tumors were characterized. Epigallocatechin gallate supplementation significantly decreased the number of leiomyomas as compared with the controls (P = .001). The tumors in the EGCG fed birds were smaller than those found in the control birds (P = .001). Serum and liver malondialdehyde and TNF-a concentrations decreased (P = .001) with EGCG supplementation. The results indicate that dietary supplementation with EGCG reduces the incidence and size of spontaneously occurring leiomyoma of the oviduct in Japanese quail. Clinical trials should be conducted to investigate the efficacy of EGCG supplementation in the prevention and treatment of uterine leiomyoma in humans. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: epigallocatechin-3-gallate; green tea; fibroid tumor; oviduct; quail